2009
DOI: 10.1007/s11771-009-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution during aging of Ti-5Al-5Mo-5V-1Cr-1Fe alloy

Abstract: The evolution of microstructure on aging of an (α+β) titanium alloy (Ti-5Al-5Mo-5V-1Cr-1Fe) in the β and (α+β) solution-treated and quenched conditions was investigated. The presence of very fine ω phase was detected by electron diffraction for samples aged below 400 ℃. The fine α aggregates are uniformly formed within β grains by nucleating at the ω particles or β/ω interfaces. At higher temperature, the formation of ω phase is avoided and the α lamellae are precipitated at the preferred site of grain boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…[9,27,28] Thermal treatments that take advantage of uniform, intragranular nucleation sites can create a fine dispersion of lamellae within the prior beta grain. In principle, the a phase could then be aged at a higher temperature to coarsen the lamellae while minimizing any formation of GBA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,27,28] Thermal treatments that take advantage of uniform, intragranular nucleation sites can create a fine dispersion of lamellae within the prior beta grain. In principle, the a phase could then be aged at a higher temperature to coarsen the lamellae while minimizing any formation of GBA.…”
Section: Methodsmentioning
confidence: 99%
“…However, population of the b grain interiors with a phase precipitates can occur by other mechanisms, as others have discussed. [6][7][8][9] For example, in many binary titanium alloys, the a phase can nucleate and grow from metastable b phase decomposition products, either x or b¢ phases. [6] The operative mechanism strongly depends on the parent b-phase composition.…”
mentioning
confidence: 99%
“…Ageing of Ti-55511 is usually performed at high temperature (>623K) where preferable nucleation sites for α nucleation already exist such as dislocations, or metastable ω phase [11]. Ohmori et al [12] have mentioned that α precipitates nucleate at ω/β interfaces, whereas Zhang et al [13] have reported that fine α phase nucleates at ω particles.…”
Section: Introductionmentioning
confidence: 99%
“…Tables 2 and 3 the width of the grain boundary α phase as well as the average β grain size of the Ti-55511 and Ti-55521 alloys, respectively after each TMP step. Since the appearance of a wide and continuous grain boundary α phase is deleterious for ductility [9][10][11], this was partially negated by near dissolution of the α phase during annealing for 120s at 1223 K (950°C), which is above the β-transus temperature (~1123 K (850°C) for the Ti-55511 alloy [19]). Prolonged heating at the super-transus temperature was deliberately avoided in order to minimise the coarsening of the β grains.…”
Section: Microstructure After Annealing and Deformation In The β Phasmentioning
confidence: 99%